Zircon U-Pb age and geochemical constraints on the origin and tectonic implication of Cadomian (Ediacaran-Early Cambrian) magmatism in SE Turkey - Beyarslan, Melahat; Lin, Yu Chin; Bingöl, Ahmet Feyzi; Chung, Sun-lin (My University, 2016)
The Bitlis-Pütürge Massifs and Derik volcanics that crop out in the Southeast Anatolian Belt are parts of the Cadomian domain in Anatolia where relicts of the oldest continental crust of Turkey are exposed. The Bitlis-Pütürge Massifs contain a Neoproterozoic basement, with overlying Phanerozoic rocks that were imbricated, metamorphosed and thrust over the edge of Arabia during the Alpine orogeny. The basement consists mainly of granitic to tonalitic augen gneisses and metagranites, associated with schists, amphibolites and paragneisses. Based on whole-rock geochemical data, the augen gneisses are interpreted to have protoliths crystallized from subduction zone magmas. This study conducted the first zircon dating on two augen gneisses that gave 206Pb/238U dates of 551 ± 6 and 544 ± 4 Ma, interpreted as the formation ages of the Pütürge Massif, broadly coeval to those of the Bitlis metagranites and the Derik volcanics that occurred from ca. 581 to 529 Ma (the Ediacaran-early Cambrian). The eHf(t) values (+1.2 to 5.3) of the dated zircons, with crustal model ages (TDM C ) from 1.4 to 1.8 Ga, indicate that formation of the Pütürge Massif involves an older, most likely the Mesoproterozoic, continental crust component. Similar to the Bitlis-Pütürge gneisses, coeval basement rocks are widespread in the Tauride-Anatolide platform (e.g., the Menderes Massif). All these dispersed Cadomian basement rocks are interpreted as fragments of the Ediacaran-Early Cambrian continental arcs bordering the active margin of northern Gondwana
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cadomian; Gneisses; Zircon U-Pb and Hf isotopes; Pütürge; SE Anatolia